Between horses and bosses: a study of the 1980 elites in Pacho, Cundinamarca - Ocampo-Méndez, Jeimy Alejandra (Sociedad y Economía, 2022)
The purpose of this article is to study the meeting of regional powers and the rising elites that emerged from the agricultural, emerald mining and drug trafficking economies in the equine scenes that took place during the 1980s in Pacho, Cundinamarca. This research contemplated different scales of observation –territorial and historical– as the micro-object, which is the Paso Fino horse and the equine scene, has a diachronic connection with history, and through its study, it is possible to analyze historical and political phenomena of the formation of regional powers and emerging elites in Colombia